Reconstructive valve surgery within 10 days of stroke in endocarditis. (July 2016) - Raman, Jai; Ballal, Apoorva; Hota, Bala; Mirza, Sara; Lai, David; Bleck, Thomas; Lateef, Omar
Background: The optimal timing of surgical treatment for infective endocarditis complicated by cerebrovascular events is controversial, largely due to the perceived risk of perioperative intracranial bleeding. Current guidelines suggest waiting 2 weeks between the diagnosis of stroke and surgery. The aim of this study was to investigate the clinical and neurological outcomes of early surgery following a stroke. Methods: This was a single-center retrospective analysis of 12 consecutive patients requiring surgery for infective endocarditis between 2011 and 2014 at Rush University Medical Center, with either ischemic ( n  = 6) and/or hemorrhagic ( n  = 6) cerebrovascular complications. All underwent computed tomographic angiography prior to early valve reconstructive surgery to identify potentially actionable neurological findings. Early valve surgery was performed for ongoing sepsis or persistent emboli. Neurologic risk and outcome were assessed pre- and postoperatively using the National Institutes of Health Stroke Scale and the Glasgow Outcome Scale, respectively. Results: All 12 patients underwent surgical treatment within 10 days of the diagnosis of stroke. Mortality in the immediate postoperative period was 8%. Eleven of the 12 patients exhibited good neurological recovery in the immediate postoperative period, with a Glasgow Outcome Scale score ≥ 3. There was no correlation between duration of cardiopulmonary bypass and neurological outcomes. Conclusion: Early cardiac surgery in patients with infective endocarditis and stroke maybe lifesaving with a low neurological risk. Comprehensive neurovascular imaging may help in identifying patient-related risk factors.